New Media and Democratic Culture: A Study Of Indonesia's Anti-Graft 'Facebook Movement' 2009 As The New 'Non-Party' Politics In Indonesia - Masduki, Masduki (English Education Department, Universitas Islam Indonesia, 2010)
Internet or Social Network Site is a new media facilitating collective action and a